Correlation of prolonged Cardiopulmonary Bypass time with Postoperative Complications - A prospective review - Ahsan Arif, Attaullah Khan Niazi, Muhammad Muneeb, Kanza Sana Umer, Akhtar Ali, Ahmed Shahbaz, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare post-operative in-hospital outcome of on pump CABG in patients with shorter CPB duration vs. patients with longer CPB duration. Methodology: In this cross sectional study conducted at Department of Cardiac Surgery, PIC, Jail Road, Lahore 182 subjects were selected using non probability Judgmental/ Purposive sampling Technique and randomly divided into two equal groups of 91 each. Group A: patients undergoing surgery for short duration of CPB < 90 minutes and half treated with Group B: patients undergoing surgery for long duration of CPB ≥ 90 minutes. Data was entered and analyzed using SPSS 25. Results: There were 133(73.08%) males and 49(26.92%) females in this study. The mean age of cases was 50.68±9.26 years with minimum and maximum age being 35 and 70 years. Mean Baseline Creatinine recorded for Group A was 0.92±0.19 and for Group B was 0.91±0.21. Mean urine output level recorded for Group A after 6 hours of CABG was 1.05±0.25 and for Group B after 6 hours of CABG was 0.85±0.24. There was a significant association in the occurrence of acute renal Injury in both groups whereas there was no significant association in the mortality of both groups. Conclusion: There was a significant difference between post-operative in-hospital renal outcomes of on pump CABG in patients with shorter CPB duration vs. patients with longer CPB duration. The results of both groups are nearly same as far as in-hospital mortality is concerned.